Sleep fragmentation induces reduction of synapsin II in rat hippocampus. Issue 2 (14th March 2014) - Park, Dong Sun; Yoon, Dae Wui; Yoo, Won Baek; Lee, Seung Ku; Yun, Chang‐Ho; Kim, Se Joong; Kim, Jin Kwan; Shin, Chol
Abstract Continuation of sleep is important for learning and memory. Some proteins are differentially expressed in specific brain regions by normal sleep/wake cycle or sleep deprivation, suggesting that specific proteins are regulated by sleep/wake cycle and could play an important role in regulation of normal brain function associated with sleep in the regions. The hippocampus is a major region of the brain accounting for memory formation and organization, and its specific function could be altered by change of synapse‐related molecular components. To examine sleep fragmentation‐induced alteration of proteins in the hippocampus, two‐dimensional gel electrophoresis was performed. Thirty‐six male Wistar rats were randomly divided into the home cage group, sleep fragmentation group, and exercise control group. Four day sleep fragmentation was accomplished by a forced walking wheel system with a wheel on/off cycle of 30‐s on/90‐s off to mimic the arousal that is common in patients with severe sleep apnea. Time interval of exercise control was set at 10 min on/30 min off. Of 58 spots that were differentially expressed among the groups, one protein was consistently reduced in the sleep fragmented group compared to other groups. The protein was identified as synapsin IIa by MALDI‐TOF mass spectrometry. Real‐time polymerase chain reaction and Western blot analysis confirmed downregulated expression of synapsin IIa and another isoform, synapsin IIb. The results suggest that sleep fragmentation induces molecular changes accounting for neurotransmitter release, integrity of the reserve synaptic vesicle pool, and synaptic plasticity.